Access to Care, Treatment Ambivalence, Medication Nonadherence, and Long‐Term Mortality Among Severely Hypertensive African Americans: A Prospective Cohort Study. Issue 8 (29th April 2015) - Young, J. Hunter; Ng, Derek; Ibe, Chidinma; Weeks, Kristina; Brotman, Daniel J.; Dy, Sydney Morss; Brancati, Frederick L.; Levine, David M.; Klag, Michael J.
<x xml:space="preserve">Abstract</x> African Americans living in poor neighborhoods bear a high burden of illness and early mortality. Nonadherence may contribute to this burden. In a prospective cohort study of urban African Americans with poorly controlled hypertension, mortality was 47.6% over a median follow‐up of 6.1 years. Patients with pill‐taking nonadherence were more likely to die (hazard ratio, 1.80; 95% confidence interval [CI], 1.18–2.76) after adjustment for potential confounders. With regard to factors related to nonadherence, poor access to care such as difficulty paying for medications was associated with prescription refill nonadherence (odds ratio [OR], 4.12; 95% CI, 1.88–9.03). Pill‐taking nonadherence was not associated with poor access to care; however, it was associated with factors related to treatment ambivalence including lower hypertension knowledge (OR, 2.97; 95% CI, 1.39–6.32), side effects (OR, 3.44; 95% CI, 1.47–8.03), forgetfulness (OR, 3.62; 95% CI, 1.78–7.34), and feeling that the medications do not help (OR, 2.78; 95% CI, 1.09–7.09). These data suggest that greater access to care is a necessary but insufficient remedy to the disparities experienced by urban African Americans with hypertension. To achieve its full promise, health reform must also address treatment ambivalence.